BACTERIAL CONJUNCTIVITIS AMONG MALNOURISHED CHILDREN: CAUSES, ASSOCIATED FACTORS, AND OPHTHALMIC ANTIBIOTIC RESISTANCE PATTERNS OF COMMON BACTERIAL ISOLATES - Al-Eryani, Sameha A.; Al-shamahi, Essam Yahiya; Al-Shamahi, Emad Hassan; Al-Shamahy, Hassan Abdulwahab; Sharaf, Mohammed Mohammed Ahmed (Universal Journal of Pharmaceutical Research, 2024)
Background and aims: More than 15 million children worldwide are thought to have one or more congenital or acquired visual impairments. If their immune system is defective due to poor nutrition, children are more susceptible to eye infections and other eye disorders. The ongoing, intense war and disruption of social services have had a clear impact on the overall health and nutritional status of children and the entire population in Yemen. Therefore, the purpose of this study was to study bacterial conjunctivitis in malnourished children by identifying bacterial causes and associated factors and determining patterns of ocular antibiotic resistance in bacterial isolates. Subject and methods: A cross-sectional study was carried out in the three selected places (Alkhpt hospital in Al-Kapt district, Al-Khamis hospital in Al-Khamisdistrict, and Al-Joumhori hospital in Al-Mahwatt city), from November 2022 until June 2023. The first clinical investigations of malnutrition and conjunctivitis were done by doctors in the hospitals and recorded in the pre-designed questionnaire. Collected eye swabs were investigated for bacteriological agents and antibiotic susceptibility according to standard laboratory methods in the National Center of Public Health Laboratories Sana’a (NCPHL). Results:The study included 351 males (46.4%) and 406 females (53.6%). 143 children (18.9%) suffer from moderate acute malnutrition (MAM) and 55 (7.3%) from severe acute malnutrition (SAM), with total global acute malnutrition equal to 198 (26.2%).There was a highly significant association of bacterial conjunctivitis with MAM (OR=3.1, p<0.0001), SAM (OR=2.9, p<0.0001), and severe stunting (OR=2.2, p<0.0001). Conclusions: The severity of acute malnutrition was very high in the study area, reaching a critical phase and exceeding the emergency threshold. The commonest causative organisms of bacterial conjunctivitis were S. aureus and Branhamella catarrahalis. Since there isn't a single medication that can effectively treat these diverse species of bacteria, it's best to look into bacteriological culture and in vitro antibiotic sensitivity. Peer Review History: Received: 4 October 2023; Revised: 9 November; Accepted: 25 December; Available online: 15 January 2024 Academic Editor: Dr. Amany Mohamed Alboghdadly , Ibn Sina National College for Medical Studies in Jeddah, Saudi Arabia, amanyalboghdadly@gmail.com Reviewers: Dr. Nkechi Obiofu Ezenobi, University of Port Harcourt, Nigeria, nkechi.ezenobi@uniport.edu.ng Dr. Nicola Micale, University of Messina, Italy, nmicale@unime.it